Design, Construction and Performance Evaluation of Motor Driven Maize Sheller - Gudina, Abdisa (ASTU, 2018)
Shelling is one of most critical post- harvest operations of grain crops. Varieties of grains are produced and shelled traditionally. The traditional shelling of maize is one of the most time consuming operations which involves drudgery, grain loss and breakage due to manual shelling by biting using a stick and using animal trampling in some places. The existing maize shellers are normally large and heavy; require high power input with high shelling capacity. Besides, the cost of purchasing such shellers is high for the rural small holder farmers. Therefore, this study aims to design, construct and evaluate the performance of small motor driven maize sheller. It was constructed from locally available materials and its cost is very low and affordable. The machine basic components are hopper, shelling unit (spike, drum and concave), outer cover, shaft, frame and outlet. The arrangement of these parts was connected by belt and pulley. A 2 hp electric motor provides drive through belt connections to drive pulley on shelling drum. The actual test was conducted using three different shelling drum peripheral speed and feed rates at 12% moisture content (wet basis).Analysis of variance (ANOVA) and Least Significant Difference (LSD) was used to determine the significant differences among treatments and to form regression equation. Levels of significance was used in F-test at (P<0.05) for the statistical analysis. Results showed that the maximum shelling efficiency of 98.78% was observed with 2000kgh-1 feed rate at10.1ms-1shelling drum peripheral speed where as it was minimum 94.20% for 1000 kg hr-1 feed rate at 9.2 ms-1shelling drum peripheral speed. The analysis of variance (ANOVA) of the results obtained at (p<0.05) probability confirmed that the shelling efficiency increases with an increase in shelling drum peripheral speed and decrease in feed rate. The output capacity ranged from 1500 kg hr-1to 2000 kghr-1 with an average value of 1800 kghr-1. Based on the performance evaluation results, it is concluded that the maize sheller prototype could be efficiently, effectively and economically used by the majority of Ethiopian farmers.

Shelling Is One Of Most Critical Post- Harvest Operations Of Grain Crops. Varieties Of Grains Are Produced And Shelled Traditionally. The Traditional Shelling Of Maize Is One Of The Most Time Consuming Operations Which Involves Drudgery, Grain Loss And Breakage Due To Manual Shelling By Biting Using A Stick And Using Animal Trampling In Some Places. The Existing Maize Shellers Are Normally Large And Heavy; Require High Power Input With High Shelling Capacity. Besides, The Cost Of Purchasing Such Shellers Is High For The Rural Small Holder Farmers. Therefore, This Study Aims To Design, Construct And Evaluate The Performance Of Small Motor Driven Maize Sheller. It Was Constructed From Locally Available Materials And Its Cost Is Very Low And Affordable. The Machine Basic Components Are Hopper, Shelling Unit (Spike, Drum And Concave), Outer Cover, Shaft, Frame And Outlet. The Arrangement Of These Parts Was Connected By Belt And Pulley. A 2 Hp Electric Motor Provides Drive Through Belt Connections To Drive Pulley On Shelling Drum. The Actual Test Was Conducted Using Three Different Shelling Drum Peripheral Speed And Feed Rates At 12% Moisture Content (Wet Basis).Analysis Of Variance (Anova) And Least Significant Difference (Lsd) Was Used To Determine The Significant Differences Among Treatments And To Form Regression Equation. Levels Of Significance Was Used In F-Test At (P<0.05) For The Statistical Analysis. Results Showed That The Maximum Shelling Efficiency Of 98.78% Was Observed With 2000kgh-1 Feed Rate At10.1ms-1shelling Drum Peripheral Speed Where As It Was Minimum 94.20% For 1000 Kg Hr-1 Feed Rate At 9.2 Ms-1shelling Drum Peripheral Speed. The Analysis Of Variance (Anova) Of The Results Obtained At (P<0.05) Probability Confirmed That The Shelling Efficiency Increases With An Increase In Shelling Drum Peripheral Speed And Decrease In Feed Rate. The Output Capacity Ranged From 1500 Kg Hr-1to 2000 Kghr-1 With An Average Value Of 1800 Kghr-1. Based On The Performance Evaluation Results, It Is Concluded That The Maize Sheller Prototype Could Be Efficiently, Effectively And Economically Used By The Majority Of Ethiopian Farmers.
Design, Construction And Performance Evaluation Of Motor Driven Maize Sheller